TEACHERS’ PERCEPTIONS OF THE IMPACT OF MICROSOFT LEARNING TOOLS IN TEACHING OF SCIENCE IN THE FCT-SENIOR SECONDARY SCHOOLS, NIGERIA - Tijjani Mohammed Mukaddas; Katcha Muhammad Abdullahi (International Journal of Arts, Sciences and Education, 2022)
Abstract Microsoft introduced immersive education solutions to equip teachers with modern tools to make their job easier and effective. Microsoft technology such as computers, smart phones, tablets or internet devices etc. Are example of Microsoft products that support educators in keeping students engaged and safe in digital classrooms. The 21st century education has required teachers and schools in Nigeria to embrace Microsoft leaning technologies to effectively engage students in various activities. This study, therefore, aimed to reveal teachers’ perceptions of the use of Microsoft products for teaching and learning of science in senior secondary schools in Federal Capital Territory, Nigeria. The descriptive survey research design was utilized and 100 science teachers from public and private schools were randomly selected using random sampling technique. E-questionnaire was used in the collection of data. Descriptive statistics were used to analyze the quantitative data. The finding of the study revealed that Microsoft products are effectively utilized by science teachers in the private schools but was not effectively available and utilized in public schools in the FCT. The result obtained revealed that Microsoft products are effective in addressing some of the major challenges encountered by teachers during teaching and learning processes. It was concluded that Microsoft need to support teachers by equipping them with affordable products that will enhance classroom organization and consequently facilitate teaching and learning processes. The study encourages wider adoption of the Microsoft tools application by schools in Nigeria.